peningkatan Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial Melalui Metode Diskusi Kelompok Kecil STUDENT TEAMS ACHIEVEMENT DIVISIONS - Ahmad Halid; Achmad Faisol; Abu Aman Siddiq Al Ghafir; Sitti Holifah Agus Niah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2021)
Improving learning outcomes depends on the teacher teaching students. teachers must have strategies so that students can learn effectively and efficiently, and can recognize the expected goals of learning that takes place in the classroom. The focus of the research is on how to improve social studies learning outcomes through the "Student Teams Achievement Divisions" small group discussion method for Class III students at SD Negeri Gambiran 03 for the academic year 2020-2021"? The purpose of this study is to improve the quality of learning on cooperative materials by using the small group discussion method "Student Teams Achievement Divisions. This study uses a qualitative approach to the type of CAR with the research subject of teachers and third grade students. data collection using interviews, observation and documentation. The results of this study show the improvement of social studies learning outcomes through the small group discussion method "Student Teams Achievement Divisions". In the third grade students of SD Negeri Gambiran 03 there was an increase, as evidenced by the increase in student learning outcomes from pre-cycle to cycle 1 which increased, from cycle 1 to cycle II also increased.